Trapezoidal broyden's method for solving systems of nonlinear equations - Mustafa, Mamat; Kabiru, Muhammad; M. Y., Waziri (2014)
We propose in this paper a Broyden- like method using the trapezoidal rule to solve system of nonlinear equations. A two point predictor- corrector approach was used, where the Broyden method is the predictor and the proposed method is the corrector. Numerical experiment carried out on some test problems with standard initial points has shown that the proposed method is very encouraging.